Exploration of novel g-C3N4/SiO2 aerogel composites for visible-light-driven degradation of methylene blue - Haonan Wu; Junfeng Li; Yue Ma; Qin Long; Peicong Zhang; Yi Huang; Jinshu Zhang; Yubin Li; Chengye Yang (AIP Advances)
Water pollution by organic dyes, such as methylene blue (MB), has become an increasingly important issue. g-C3N4/SiO2 aerogel composites exhibit potential for removing organic dyes but are still limited by their small specific surface area and low photochemical efficiency. In this study, we propose an approach for preparing g-C3N4/SiO2 aerogel composites by combining sol-gel and calcination processes to optimize the materials’ adsorption and photocatalytic synergistic effects by structural design. In g-C3N4/SiO2 composites, the layered g-C3N4 nanosheets grew uniformly on the surface and inside the SiO2 three-dimensional network structure. Among them, the 20-g-C3N4/SiO2 showed the highest MB degradation efficiency, with a specific surface area of 151.5 m2/g and a pore diameter of 11 nm. Under visible light, it achieved 92% MB degradation at a dosage of 0.2 g/l and 50 mg/l initial concentration, which was 6.1 times the degradation rate of g-C3N4 and 3.4 times the adsorption rate of SiO2 aerogel. Moreover, the material exhibited excellent cyclic stability and degraded 85% of the MB after three cycles. The g-C3N4/SiO2 composites effectively adsorbed and focused MB on their surfaces because of their superior adsorption capacity facilitated in situ photocatalytic degradation under visible light. This process achieved efficient degradation of high concentrations of MB, indicating potential application value in the removal of organic dyes from water.